Production of specific brucellin to diagnose Brucellosis - Baghdad Science Journal (مجلة بغداد للعلوم)
act : A soluble cytoplasmic antigen (Brucellin) was prepared from Brucella melitensis Rev1 and used to diagnose brucellosis in experimentally infected mice with virulent strains of Brucella melitensis and Brucella abortus two weeks after infection. The best result was obtained with the third peak of the four peaks. All four peaks were used as antigen for skin test in a group of mice two weeks after vaccinated with S19 vaccine and the best result was obtained with third peak. All four peaks were also used as antigen for skin test in a group of mice previously vaccinated with Listeria monocytogenes live attenuated vaccine. All four fractions of the extracted brucellin antigens exhibited a negative skin test result in Listeria monocytogenes experimentally vaccinated mice.